Programming WCF services - Löwy, Juval (O'Reilly, 2007)
Written by Microsoft software legend Juval Lowy, Programming WCF Services is the authoritative introduction to Microsoft's new, and some say revolutionary, unified platform for developing service-oriented applications (SOA) on Windows. Relentlessly practical, the book delivers insight, not documentation, to teach developers what they need to know to build the next generation of SOAs. Not only will this book make you a WCF expert, it will deliver techniques and guidance to become a better software engineer. It's the Rosetta Stone of WCF.